Water-steam activation toward oxygen-deficient vanadium oxides for enhancing zinc ion storage. Issue 43 (28th October 2021) - Yang, Hailun; Ning, Pengge; Zhu, Zewen; Yuan, Ling; Jia, Wenting; Wen, Jiawei; Xu, Gaojie; Li, Yuping; Cao, Hongbin
Abstract : This study provides a novel water-steam activation strategy in oxygen-deficient vanadium oxides for promoting zinc ion reversible (de)intercalation for high performance aqueous zinc-ion batteries. Abstract : A major limitation of vanadium oxides in aqueous Zn/V2 O5 ion battery applications is that they suffer from strong coulombic ion–lattice interactions with divalent Zn 2+ . Correspondingly, vanadium oxides show the poor utilization of their electrochemically active surface areas and unsatisfactory structural stability. The Gibbs free energy of Zn 2+ adsorption in the vicinity of oxygen vacancies can be reduced to a thermoneutral value, which suggests that the Zn 2+ adsorption/desorption process on the oxygen-deficient oxide lattice is more reversible as compared to a less defective vanadium oxide. In this work, it is demonstrated that these problems can be significantly ameliorated via creating oxygen vacancies in vanadium oxide host materials. Specifically, for the first time, vanadium oxides with abundant oxygen defects (labeled Vo -V2 O5 ) are fabricated via a new water-steam activation strategy. Such water-steam activation forms abundant oxygen defects, and the as-prepared materials show a 3.5-fold increase in the carrier density, together with larger electrochemically active surface areas compared to a less defective vanadium oxide. When used as a cathode material for aqueous zinc ion batteries, Vo -V2 O5 exhibits a high specific capacity (335 mA h g −1 at 0.2 A g −1 ) and excellent cell stability (∼87.2% capacity retention after 3500 continuous charge/discharge cycles at 5.0 A g −1 ). Thus, this water-steam activation approach for disordered metal oxides yields highly competitive cathode materials, which may also aid in the future development of advanced materials in related energy fields.